MAKNA PESAN DALAM DINAMIKA KONFLIK INTERPERSONAL PADA FILM WEB SERIES “TERIMA KOST PUTRI” - Gunawan, Muhammad Khalil (Wardah, 2024)
Significant changes in the film industry encourage access via the YouTube platform and are no longer limited to the big screen. The current development of YouTube in Indonesia, with the emergence of web series on YouTube channels, has become a popular way to pass the time or relax after activities. Web series films are a form of public viewing that incorporates modern concepts. The researchers researched the web series "Terima Kost Putri" on YouTube, uploaded by @JalangkoteRasaKeju, which explores the theme of conflict in interpersonal relationships. This study aims to uncover the message hidden in the dynamics of interpersonal conflict depicted by the characters Rima and Nisa in the web series film "Terima Kost Putri." The researcher then used qualitative methods. The first and second episodes were chosen as study materials to identify scenes of conflict between Rima and Nisa, which were then analyzed using Charles Sanders Peirce's semiotics. The Triadic model has three main components: Representation (Sign), Object, and Interpretant. The analysis shows that the first message has three meanings based on the An Expressed Struggle aspect. First, the meaning of interpersonal conflict messages can be seen in their differences in background, preferences, and values. Rima is not interested in Korean films or music. On the contrary, Nisa likes Korean films and music. Second, based on the Perceived Scarce Resources and Interference aspects of interpersonal conflict messages, there are differences in urgent interests and the influence of socio-cultural status, where Nisa needs to use the toilet while Rima is still using it. Third, the relevant aspects of interpersonal conflict of Perceived Scarce Resources and Interference reappeared, where the meaning of interpersonal conflict messages based on the lack of open communication between them becomes an obstacle. Nisa showed emotional irritation when she found Rima left trash in front of her room and used her glass.